Sustainability at UAM-Azcapotzalco for academic programs with virtual classroom methodologies - González-Sosa, Jesús Vicente; Zavala-Osorio, Yadira (Journal of Sustainability Perspectives, 2023)
Abstract. The post-pandemic educational processes due to Covid-19 have generated an interest in structuring new learning trends. The Autonomous Metropolitan University (UAM) Azcapotzalco identified the use of methodologies with digital tools known as virtual classrooms during the pandemic to continue academic activities. These digital tools are still being used in different academic programs, including undergraduate and postgraduate programs to promote the professionalism of the university community. This paper provides a general breakdown of the virtual classroom format as a methodology in the teaching-learning processes to improve the educational environment at a higher level and ensure educational sustainability through the innovation of new technologies and digital tools that can be applied at a national and international level. The expected results from this methodology are part of an improvement process aimed at generating academic programs in virtual environments to enrich the educational models at higher and postgraduate levels and creating collaborative groups within each teaching department that can be extrapolated to a unit or campus level.Keyword:Sustainable Academic, Educational Methodology, Educational Process, Virtual Classroom.